Ardebil's Cultural Situation Based on Biographical Figures from the Early Centuries to the Tenth Century - Fateme Jafarnia (پژوهش های تاریخی, 2017)
With the entry of Islam into Iran for about two centuries, Iranians did not have much role in political and administrative relations, but with the arrival of the Abbasids, the Iranian influence in the political and cultural arenas was emerged. The Iranian employment of the scientists from the very beginning, on the one hand, and the attention of the caliphs to the religious education of the people of the lands that were flourishing from the beginning of the conquests on the other hand, led to the spread of religious sciences in Iran. Science was the first means of communication for Iranians to participate in the Islamic government. Iranians played a significant role during the formation of Islamic civilization and, of course, along with other peoples and nations. Meanwhile, various regions of Iran, including Ardebil, based on the political-cultural conditions, have influenced the formation of Islamic civilization. According to the author of the paper, by investigating the biographies of Ardebili scholars, one can find that the scientists of Ardebil were in the flourish of a bunch of sciences. Also, the strategic situation and political events in the region, as well as the lack of dynamism and prosperity of Ardebil scientific centers, have affected the cultural situation in the region. The result shows that the scientists of the region have had the most activity in the field of Islamic sciences, especially mysticism and hadith. Also, due to the political instability and lack of dynamism of the scientific centers of the region, many Ardebili scientists have migrated and the scientific centers of the region have not been much considered by scientists in other regions.